2018
DOI: 10.1093/brain/awx353
|View full text |Cite
|
Sign up to set email alerts
|

Networks of tau distribution in Alzheimer’s disease

Abstract: See Whitwell (doi:10.1093/brain/awy001) for a scientific commentary on this article.A stereotypical anatomical propagation of tau pathology has been described in Alzheimer's disease. According to recent concepts (network degeneration hypothesis), this propagation is thought to be indicative of misfolded tau proteins possibly spreading along functional networks. If true, tau pathology accumulation should correlate in functionally connected brain regions. Therefore, we examined whether independent components cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
104
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 58 publications
(46 reference statements)
12
104
3
Order By: Relevance
“…Thanks to the recent development of tau PET tracers, it is now possible to measure the regional distribution and topological patterns of tau, and assess how they are related to other biomarkers of early AD [3]. However, so far, most tau PET studies in older adults have focused on a single brain area or independent regions of interest, despite growing evidence that tau deposits in different areas are not independent from each other but are strongly correlated, forming spatial patterns or covariance networks [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the recent development of tau PET tracers, it is now possible to measure the regional distribution and topological patterns of tau, and assess how they are related to other biomarkers of early AD [3]. However, so far, most tau PET studies in older adults have focused on a single brain area or independent regions of interest, despite growing evidence that tau deposits in different areas are not independent from each other but are strongly correlated, forming spatial patterns or covariance networks [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the regional pattern of Aβ deposition is consistent across clinical phenotypes of AD and is not related to neurodegeneration (Bischof et al, 2016; Iaccarino et al, 2018; La Joie et al, 2012; Ossenkoppele et al, 2015; Ossenkoppele et al, 2016; Rabinovici et al, 2008), while tau topographically matches grey matter atrophy and glucose hypometabolism and can therefore be interpreted as the likely driving force behind neurodegeneration (Dronse et al, 2017; Ossenkoppele et al, 2016; Jennifer L Whitwell et al, 2018; Xia et al, 2017). Additionally, it has been observed that AD pathological proteins may spread along functional brain networks, with strongly connected regions displaying a higher tau burden (Cope et al, 2018; Hoenig et al, 2018; Jones et al, 2017) and amyloid being a partial mediator between functional network failure and tau deposition (Jones et al, 2017). The majority of these studies have assessed the spectrum of AD clinical presentations, including both typical and atypical variants.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study combining tau-PET and resting-state fMRI cross-sectionally in a small sample of AD patients found tau deposition to be preferentially distributed within the boundaries of fMRI-detected functional brain networks, i.e. within regions that are functionally connected 18 . We reported previously in cognitively normal elderly individuals and patients with AD or vascular cognitive impairment that higher inter-regional tau covariance (i.e.…”
mentioning
confidence: 99%